Attitudes of Islamic science teachers at the secondary stage in Almadinah Almonawarah towards voluntary work - Al-Ofi, Shuaa Ali; Al-Shanqeeti, Aminah Mohmmed Al-Mukhtar (Journal of Educational and Psychological Sciences, 2022)
This study aims at investigating the Islamic sciences teachers attitudes towards voluntary work, in order to achieve the purpose of the study I use the descriptive analytical approach and design questionnaire includes 25 articles divided into three domains. The sample of the study consists of (2126) teachers chosen by using simple random sampling from the teachers of Islamic sciences at the secondary stage in Madina El-Monawara. The research is come out with the following results: the Islamic sciences teachers attitudes at the secondary stage towards voluntary work related to Islamic domain come with verbal connotation (very high), the Islamic sciences teachers attitudes at the secondary stage towards voluntary work related to teaching domain come with verbal connotation (very high), the Islamic sciences teachers attitudes at the secondary stage towards voluntary work related to social domain come with verbal connotation (very high). There are no statistically significant differences at the level of significance (0.05) between the averages of the respondents' responses to the attitudes of Islamic science teachers at the secondary stage towards voluntary work which due to the variable of academic qualification and years of service. According to the results a sit of recommendations. were made, including: Encouraging female teachers of Islamic sciences at the secondary stage to translate their attitudes towards volunteering into actual practices, and creating educational requirements concerned with studying volunteering in teacher training programs, and their in-service training programs.
Keywords: Attitudes; Islamic sciences teachers; Voluntary work; Secondary stage